IMPLEMENTASI KOMIK SAINS BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN LITERASI SAINS DAN LITERASI DIGITAL SISWA SEKOLAH DASAR - Khairunnisak; Kiki Fajariani; Imam Muslem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of Augmented Reality-based science comic media in improving the scientific literacy and digital literacy of fifth-grade students at SD Negeri 3 Percontohan. The problem addressed in this study is the limited use of interactive and visual learning media in science learning, which often makes students experience difficulty in understanding abstract science concepts and using digital technology for educational purposes. This research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The subjects were 32 fifth-grade students. Data were collected through scientific literacy tests, digital literacy questionnaires, observation sheets, student response questionnaires, and documentation. The data were analyzed by comparing pretest and posttest scores and calculating the N-Gain score. The results showed that students’ average scientific literacy score increased from 58.25 in the pretest to 82.50 in the posttest, with an N-Gain score of 0.58 in the medium category. Students’ digital literacy score also increased from 61.40 to 84.10, with an N-Gain score of 0.59 in the medium category. Observation results indicated that students’ learning activities were in the good to very good category, while students’ responses to the media were in the very good category. Therefore, Augmented Reality-based science comic media is considered effective in supporting science learning by providing a more visual, interactive, enjoyable, and meaningful learning experience.